Lily pollen alkaline phytase is a histidine phosphatase similar to mammalian multiple inositol polyphosphate phosphatase (MINPP) - Mehta, B.D.; Jog, S.P.; Johnson, S.C.; Murthy, P.P.N.
Phytic acid is the most abundant inositol phosphate in cells; it constitutes 1-5(percent)of the dry weight of cereal grains and legumes. Phytases are the primary enzymes responsible for the hydrolysis of phytic acid and thus play important roles in inositol phosphate metabolism. A novel alkaline phytase in lily pollen (LlALP)was recently purified in our laboratory. In this paper, we describe the cloning and characterization of LlALP cDNA from lily pollen. Two isoforms of alkaline phytase cDNAs, LlAlp1 and LlAlp2, which are 1467 and 1533 bp long and encode proteins of 487 and 511 amino acids, respectively, were identified. The deduced amino acid sequences contains the signature heptapeptide of histidine phosphatases, -RHGXRXP-, but shares <25 percent identity to fungal histidine acid phytases. Phylogenetic analysis reveals that LlALP is most closely related to tiple inositol polyphosphate phosphatase (MINPP)from humans (25 percent)and rats (23 percent). mRNA corresponding to LlAlp1 and LlAlp2 were expressed in leaves, stem, petals and pollen grains. The expression profiles of LlAlp isoforms in anthers indicated that mRNA corresponding to both isoforms were present at all stages of flower evelopment. The expression of LlAlp2 cDNA in Escherichia coli revealed the accumulation of the active enzyme in inclusion bodies and confirmed that the cDNA encodes an alkaline phytase. In summary, plant alkaline phytase is a member of the histidine phosphatase family that includes MINPP and exhibits properties distinct from bacterial and fungal phytases.
Keywords: LILIUM LONGIFLORUM; LILIACEAE; EASTER LILY; POLLEN GRAINS; CLONING; ALKALINE PHYTASE; RECOMBINANT EXPRESSION; MULTIPLE INOSITOL POLYPHOSPHATE; PHOSPHATASE (MINPP)